Odpowiedzi

Najlepsza Odpowiedź!
2010-02-10T17:43:17+01:00
A)3x+2y=13
2x+y=11/*-2

3x+2y=13
-4x-2y=-22

-1x=9/:-1
x=-9

3x+2y=13
3*(-9)+2y=13
-27+2y=13
2y=40/:2
y=20

x=-9
y=20


b) 5x+3y=0
-x-2y=7/*5

5x+3y=0
-5x-2y=35

1y=35

5x+3y=0
5x+3*35=0
5x=-105
x=-21

x=-21
y=35

c) 3u+2v=2/*-2
5u+4v=6

-6u-4v=-4
5u+4v=6

-1u=2/*-1
u=-2

5u+4v=6
5*-2+4v=6
-10+4v=6
4v=16/4
v=4

u=-2
v=4

d) 3s+5t=-6/*2
1,5s-2t=-3/*5

6s+10t=-12
7,5s-10=-15

13,5s=-27/:13,5
s=2

3s+5t=-6
3*2+5t=-6
5t=-12/:5
t=2,4

e) 5=3x-y
5x-2y=7

-3x+y=-5/*2
5x-2y=7

-6x+2y=-10
5x-2y=7

-1x=-3/:-1
x=3

5x-2y=7
5*3-2y=7
-2y=-8/:-2
y=4

x=3
y=4

f) x-3y=5
y+3x=-5

x-3y=5
3x+y=-5/*3

x-3y=5
9x+3y=-15

10x=-10/:10
x=-1

y+3x=-5
y+3*(-1)=-5
y+(-3)=-5
y=2

x=-1
y=2
5 4 5